Illicit Enrichment Conception in Positive Law in Indonesia - Juwita Widya Mahmud; Mohamad. R. U Puluhulawa; Waode Mustika (Universitas Negeri Gorontalo, 2023)
This study aims to determine the Regulation of Article 20 of the United Nations Convention Against Corruption (UNCAC) concerning Illicit Entrichment in Positive Law in Indonesia. The method used in this study is a type of normative juridical research that uses a legal approach to views and doctrines. The results of this study show that Indonesia's current positive law does not contain regulations related to Article 20 of the United Nations Convention Against Corruption (UNCAC) on the acquisition of assets of public officials (Illicit Enrichment) which allows asset seizure if the state official cannot explain the cause of the increase in assets related to his legitimate income. However, in Indonesia's positive law, there are relevant regulations close to those in Article 2 paragraph (1), Article 18, and Article 37 of the Corruption Eradication Law